Cytotoxicity of Moringa Plants ( Moringa Oleifera L.) on Cancer Cells - Haryoto, Haryoto; Suranto, Choirun Nisa (Journal of Nutraceuticals and Herbal Medicine, 2024)
Moringa ( Moringa oleifera L.) is one of the herbal plants that grows in Indonesia. Moringa oleifera has many properties, namely that it can act as an antidiabetic, antibacterial, antitumor, antipyretic, antiepileptic, antiinflammatory, antiulcer, antispasmodic, diuretic, antihypertensive, cholesterol lowering, antioxidant, hepatoprotective, antifungal. The aim of preparing this review is to determine the cytotoxic activity of Moringa oleifera L.) and the mechanism of action of secondary metabolites that can be isolated from Moringa. The preparation of this review comes from articles obtained through the Google Scholar database , PubMed and Sciencedirect with the keywords namely " Cytotoxic AND " Moringa oleifera lam" AND Anticancer AND IC50 values ". The inclusion criteria set were original articles or articles full text in PDF format regarding the potential cytotoxic activity of the Moringa oleifera L. plant in vitro with a publication year range of 2012-2021, using the MTT assay method , has an IC value of 50 < 50 µg/mL in the leaves and seeds and has an IC value 50 < 100 µg/mL in other plant parts . From these criteria, 10 suitable articles were obtained . The results of the analysis show that the cytotoxic activity of M. oleifera against several cancer cells can be categorized as active to very active . Next, it can be seen if it has anticancer activity M. oleifera is obtained from secondary metabolites resulting from extraction M. oleifera . Secondary metabolites that have been isolated from M. oleifera is known to contain lectins, routine, quercetin, astragalin, isoquercetin, glucomoringin, 7-Octenoid Acid, Oleamide, and 1-Phenyl-2-Pentanol. This metabolite has an anticancer mechanism in the form of inducing apoptosis through : (1 ) ROS -mediated signaling pathways , (2) targeting the anti-apoptotic protein BCL-2 family, (3) regulation of the tumor suppressor protein p53, (4) inhibition of NF- κB, and ( 5) decrease in MAPK signal.